Kaempferol From Penthorum chinense Pursh Attenuates Hepatic Ischemia/Reperfusion Injury by Suppressing Oxidative Stress and Inflammation Through Activation of the Nrf2/HO-1 Signaling Pathway - Yifan Chen; Tongxi Li; Peng Tan; Hao Shi; Yonglang Cheng; Tianying Cai; Junjie Bai; Yichao Du; Wenguang Fu; Wenguang Fu (Frontiers Media S.A., 2022)
The purpose of this study is to investigate the protective effect of kaempferol (KAE), the main active monomer from Penthorum chinense Pursh, on hepatic ischemia/reperfusion injury (HI/RI) and its specific mechanism. HI/RI is a common complication closely related to the prognosis of liver surgery, and effective prevention and treatment methods are still unavailable. Ischemia/reperfusion (I/R) injury is caused by tissue damage during ischemia and sustained oxidative stress and inflammation during reperfusion. Penthorum chinense Pursh is a traditional Chinese medicine widely used to treat liver disease since ancient times. Kaempferol (KAE), a highly purified flavonoid active monomer isolated and extracted from Penthorum chinense Pursh, was investigated for its protective effect on HI/RI. Our study indicates that KAE pretreatment alleviated I/R-induced transaminase elevation and pathological changes. Further analysis revealed that KAE pretreatment attenuates I/R-induced oxidative stress (as measured by the content of MDA, SOD and GSH) in vivo and reduces hypoxia/reoxygenation (H/R) -induced reactive oxygen species (ROS) generation in vitro. Meanwhile, KAE inhibits activation of NF-κB/p65 and reduces the release of pro-inflammatory factors (TNF-α and IL-6) to protect the liver from I/R-induced inflammation. Nuclear erythroid 2-related factor 2 (Nrf2) is a crucial cytoprotection regulator because it induces anti-inflammatory, antioxidant, and cytoprotective genes. Therefore, we analyzed the protein levels of Nrf2 and its downstream heme oxygenase-1 (HO-1) in the liver of mice and hepatocytes of humankind, respectively, and discovered that KAE pretreatment activates the Nrf2/HO-1 signaling pathway. In summary, this study confirmed the hepatoprotective effect of KAE on HI/RI, which inhibits oxidative stress and inflammation by activating the Nrf2/HO-1 signaling pathway.